2008
DOI: 10.1038/nm.1888
|View full text |Cite|
|
Sign up to set email alerts
|

BMP type I receptor inhibition reduces heterotopic ossification

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a congenital disorder of progressive and widespread postnatal ossification of soft tissues 1-4 and is without known effective treatments. Affected individuals harbor conserved mutations in the ACVR1 gene that are thought to cause constitutive activation of the bone morphogenetic protein (BMP) type I receptor, activin receptor-like kinase-2 (ALK2)5. Here we show that intramuscular expression in the mouse of an inducible transgene encoding constitutively active ALK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
624
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 562 publications
(640 citation statements)
references
References 34 publications
14
624
2
Order By: Relevance
“…This process occurs in two separate patient populations: those with severe trauma, including large surface-area burns, musculoskeletal injury, orthopedic operations, and even spinal cord injury; and those with a genetic disease known as fibrodysplasia ossificans progressiva (FOP) (1)(2)(3)(4). FOP is caused by a hyperactivating mutation in the type I bone morphogenetic protein (BMP) receptor ACVR1 (Activin type 1 receptor), and patients with FOP develop ectopic bone lesions in the absence of any substantial trauma.…”
mentioning
confidence: 99%
“…This process occurs in two separate patient populations: those with severe trauma, including large surface-area burns, musculoskeletal injury, orthopedic operations, and even spinal cord injury; and those with a genetic disease known as fibrodysplasia ossificans progressiva (FOP) (1)(2)(3)(4). FOP is caused by a hyperactivating mutation in the type I bone morphogenetic protein (BMP) receptor ACVR1 (Activin type 1 receptor), and patients with FOP develop ectopic bone lesions in the absence of any substantial trauma.…”
mentioning
confidence: 99%
“…In vitro and in vivo models suggest that small-molecule inhibition of BMP type I receptors can downregulate BMP signaling, and thus may be useful in treating HO syndromes. Furthermore, heterozygous mutations in the ACVR1 gene encoding for the BMP type I receptor ALK2 have been shown to be key in the genetics of fibrodysplasia ossificans progressiva (FOP) and therefore offer potential future therapeutic targets to inhibit excess bone formation [13]. BMP-4 is involved in physiological skeletogenesis and disease such as FOP.…”
Section: Bmp Type 1 Receptor Inhibition and Bmp Antagonist Nogginmentioning
confidence: 99%
“…Different evidences suggested that dorsomorphin binds the ATP binding site in the kinase domain of the type I BMP receptors (ALK1, ALK2, ALK3 and ALK6) [98]. Latest studies demonstrated that dorsomorphin appears to be a poor candidate for clinical development, because it is well known that inhibits AMP activated kinase (AMPK) [160] and also exhibit significant activity on several tyrosine kinase receptors [98,161]. Nevertheless, further development of small molecule compounds with a narrower inhibition profile of BMP type I receptors is being pursued.…”
Section: Applications Of Small Molecule Bmp Inhibitors In Human Pathomentioning
confidence: 99%
“…Through a structure-activity relationship study of dorsomorphin derivatives, an optimized compound (LDN-193189, Figure 3) with higher activity and specificity on BMP type I receptors has been developed [161], although its potential effects on other protein kinases is not completely excluded [162]. In spite of their potential effects on other kinases different from the BMP pathways, these inhibitors are potentially effective for some clinical disorders.…”
Section: Applications Of Small Molecule Bmp Inhibitors In Human Pathomentioning
confidence: 99%